The influence of family in children’s feeding difficulties: an integrative review - da Fonseca, Pâmela Gracielle; Raposo, António; Alqarawi, Nada; Alasqah, Ibrahim; Pinto, Mariana Figueiredo; Martins, Tábata Monaliza Marcelino; Gonçalves, Viviane Dias; Pereira, Simone Cardoso Lisboa; Albaridi, Najla A.; BinMowyna, Mona N.; Saraiva, Ariana; Guimarães, Nathalia Sernizon (Frontiers in Pediatrics, 2025)
BackgroundFeeding difficulties, such as limited appetite, selective eating, and food phobia, affect caregivers' ability to provide adequate nutrition to children. These issues impact 25%–40% of non-neurodivergent children and up 80% of neurodivergent children.AimThis review examines how family involvement influences the improvement, worsening, or maintenance of feeding difficulties in neurodivergent and non-neurodivergent preschool and school-age children.MethodsAn integrative review was conducted using Embase, PubMed, Scopus, Cochrane Library, Lilacs and grey literature (Google Scholar and Connect Papers). The review focused on randomized clinical trials (RCTs) involving parents or caregivers of children aged 2–10 years, assessing lifestyle or psychological interventions.ResultsFrom 1,257 studies, 885 primary articles were screened. Of the 100 most recent articles on grey literature, 2 met the eligibility criteria after full-text assessment and were therefore included in the review. Thirty-six studies were reviewed in full, leading to 11 RCTs with 630 children aged 1 to 14. Interventions included behavioral education, sensory education, and cooking classes. Findings indicated increased vegetable acceptance in two studies, improved feeding difficulties scores in five, and reduced avoidant/restrictive food intake disorder (ARFID) symptoms in two studies. One study showed no significant differences between control and intervention groups.ConclusionFamily-involved interventions generally produced positive outcomes in managing feeding difficulties. However, methodological variability and the predominance of studies from high-income countries limit the generalizability of these results. Future research should focus on standardizing diagnostic criteria and developing culturally sensitive interventions.